Emerging trends and thematic evolution of immunotherapy for glioma based on the top 100 cited articles - Zhou, Yan; Liu, Min; Huang, Xing; Liu, Zhen; Sun, Yun; Wang, Minjie; Huang, Tao; Wang, Xianke; Chen, Long; Jiang, Xiaobing (Frontiers in Oncology, 2024)
Purpose: This study aims to depict the scientific advancements in immunotherapy for glioma by analyzing the top 100 most frequently cited articles over the past 20 years.Methods: Top 100 most influential papers in immunotherapy for glioma were identified from the Web of Science Core Collection. Citations, countries/regions, institutions, journals, authorships, keywords and references were extracted and analyzed by CiteSpace, VOSviewer, R software and an online bibliometric platform.The United States possessed a robust global presence, leading in terms of publications and maintaining strong collaborative ties with numerous countries. The institution that made the greatest contributions was Duke University, with 16 papers.Heimberger AB, Sampson JH and Reardon DA secured the top three positions with 15, 12, and 11 papers, respectively. "Macrophage ontogeny", "microglia", "polarization", "mass cytometry", "tumor mutation burden", "sensitivity", "msh6", "pd-1 blockade" and "dna repair" were the recent hot keywords. "Microglia" and "polarization" as the emerging research directions should be given more consideration.This is the first bibliometric analysis to identify the top 100 papers on immunotherapy for glioma. "Microglia" and "polarization" will be hotspots for future research. The clinical efficacy of glioma immunotherapy is not yet satisfactory, and there is an urgent need to search for more tumor specific antigens and targets that can assist in early diagnosis, precise treatment, prognosis, and recurrence prediction of glioma.